2019
DOI: 10.14482/psdc.35.3.155.2
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning, differentiation of self and career adaptability of brazilian university students

Abstract: psicología desde el caribe issn 0123-417x (impreso) issn 2011-7485 (on line) Volumen 35, n.º 3, septiembre-diciembre de 2018 http://dx. ResumoEmbora a influência da família no desenvolvimento de carreira seja consolidada pela literatura científica, essa interface ainda é pouco explorada a partir da teoria familiar sistêmica, principalmente no contexto brasileiro. O objetivo deste estudo foi analisar as relações entre funcionamento familiar, diferenciação do self e adaptabilidade de carreira de universitários. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previous research has indicated that higher DoS predicts higher career adaptability in the context of healthy family functioning (Fiorini & Patta Bardagi, 2018). For instance, married Turkish couples with higher DoS reported higher career adaptability (Akün et al, 2023).…”
Section: Dos To Career Adaptability (Hypothesis 1)mentioning
confidence: 94%
“…Previous research has indicated that higher DoS predicts higher career adaptability in the context of healthy family functioning (Fiorini & Patta Bardagi, 2018). For instance, married Turkish couples with higher DoS reported higher career adaptability (Akün et al, 2023).…”
Section: Dos To Career Adaptability (Hypothesis 1)mentioning
confidence: 94%